Bean (P. vulgaris) distribution in Africa : First approximation - Gray, J. (International Center for Tropical Agriculture, 1990)
These notes are intended to accompany the bean distribution map. They include comments on the production and limitations of the map, detail of the data sources, and notes on the perceived accuracy of the map for each country. There are also brief summaries of the cultivation methods and practices for some of the countries. In its current state the map is regarded only as an approximation of bean (P. vulgaris) distribution in Africa. The data, particularly for the south and west of the continent, is not very reliable (Appendix 2). Data for Cameroon is as yet, unavailable. It is known, however, that sizeable areas of beans are grown in the north and north-west of the country. It is expected that there are also areas of beans in western and south-western Africa, however, data is unavailable. Throughout, beans refers exclusively to Phaseolus vulgaris. The map gives a relatively accurate impression of the bean distribution pattern across the continent. For the countries in which CIAT currently works, the data and back-up information is good and enables relatively accurate maps to be plotted at any scale. Overall, the map is as detailed and accurate as possible, given the current availability of data. (AS)